2016
DOI: 10.1177/0883073816668774
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Low-Dose Corticosteroid Therapy Versus High-Dose Corticosteroid Therapy in Bell’s Palsy in Children

Abstract: Bell's palsy is the most common cause of acute peripheral facial nerve paralysis, but the optimal dose of corticosteroids in pediatric patients is still unclear. This retrospective study aimed to evaluate the efficacy of low-dose corticosteroid therapy compared with high-dose corticosteroid therapy in children with Bell's palsy. Patients were divided into 2 groups based on the dose of oral prednisolone regimen initiated. The severity of idiopathic facial nerve paralysis was graded according to the House-Brackm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…However, steroid is widely used in the treatment of Bell's palsy in children, and the dosage is unclear. Arican et al 27 compared the patients treated with 1 mg/kg/d prednisolone to 2 mg/ kg/d prednisolone in terms of recovery rate, and they found no significant difference in complete recovery between the groups. In our study, although the early recovery rate was statistically significant in patients who received 1 mg/kg/d prednisolone (P ¼ .04), according to the multiple logistic regression model, the effect of steroid dosage (1 mg/kg/d vs 2 mg/kg/d) on early recovery was not detected.…”
Section: Discussionmentioning
confidence: 99%
“…However, steroid is widely used in the treatment of Bell's palsy in children, and the dosage is unclear. Arican et al 27 compared the patients treated with 1 mg/kg/d prednisolone to 2 mg/ kg/d prednisolone in terms of recovery rate, and they found no significant difference in complete recovery between the groups. In our study, although the early recovery rate was statistically significant in patients who received 1 mg/kg/d prednisolone (P ¼ .04), according to the multiple logistic regression model, the effect of steroid dosage (1 mg/kg/d vs 2 mg/kg/d) on early recovery was not detected.…”
Section: Discussionmentioning
confidence: 99%
“…Another prospective study of children <15 years of age from Germany showed a recovery rate of 97% without any use of steroids [ 1 ]. Unlike this previous study, Arican et al [ 11 ] reported that oral corticosteroid was highly effective in the treatment of Bell’s palsy in children, even at a dose of 1 mg/kg/day of oral prednisolone.…”
Section: Discussionmentioning
confidence: 63%
“…Chen and Wong [ 10 ] showed that the mean age of Bell’s palsy onset in children was 6 years 7 months, 52% of patients were male, and that 44.4% of patients had right-sided Bell’s palsy. In another study, Arican et al [ 11 ] reported that the mean age of Bell’s palsy onset was 11 years, 59% of patients were female, and that 47% of patients had right-sided Bell’s palsy. In our study, the mean age of Bell’s palsy onset was 7 years 4 months, 50% of patients were female, and 49% of patients showed right-sided Bell’s palsy.…”
Section: Discussionmentioning
confidence: 99%
“…Once she was diagnosed with both conditions, she was prescribed a 10-day course of acyclovir 400 mg TID and a 14-day tapering course of PO prednisone. Corticosteroids for acute Bell's palsy are recommended to improve long-term recovery in adults and children,13 14 and recent research shows moderate evidence that corticosteroid plus antiviral treatment increases complete recovery with no significant adverse events 15. In addition, there has been some evidence, although not yet conclusive, that acyclovir may reduce the duration and pruritus of PR, and a low dose (as prescribed here) is as effective as a higher dose in achieving outcomes 16.…”
Section: Treatmentmentioning
confidence: 91%